Loco-regional recurrence trend and prognosis in young women with breast cancer according to molecular subtypes: analysis of 1099 cases - Li, Yang; Lu, Su; Zhang, Yuhan; Wang, Shuaibing; Liu, Hong (World journal of surgical oncology, 2021)
The number of young patients diagnosed with breast cancer is on the rise. We studied the rate trend of local recurrence (LR) and regional recurrence (RR) in young breast cancer (YBC) patients and outcomes among these patients based on molecular subtypes. A retrospective cohort study was conducted based on data from Tianjin Medical University Cancer Institute and Hospital for patients ≤ 35 years of age with pathologically confirmed primary invasive breast cancer surgically treated between 2006 and 2014. Patients were categorized according to molecular subtypes on the basis of hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) status. The 5-year rates for LR, RR, and distant metastases (DM) were estimated by Kaplan-Meir statistics. Nelson-Aalen cumulative-hazard plots were used to describe local recurrence- and distant metastasis-free intervals. We identified 25,284 patients with a median follow-up of 82 months, of whom 1099 (4.3%) were YBC patients ≤ 35 years of age. The overall 5-year LR, RR, and DM rates in YBC patients were 6.7%, 5.1%, and 16.6%, respectively. The LR and RR rates demonstrated a decreasing trend over time (P = 0.028 and P = 0.015, respectively). We found that early-stage breast cancer and less lymph node metastases increased over time (P = 0.004 and P = 0.007, respectively). Patients with HR-/HER2+ status had a significantly higher LR (HR 20.4; 95% CI, 11.8-35.4) and DM (HR 37.2; 95% CI, 24.6-56.3) at 10 years. Breast-conserving surgery (BCS) or mastectomy did not influence rates of LR and RR. In the overall population, the 5-year survival of YBC patients exceeded 90%. The rates of LR and RR with YBC patients demonstrated a downward trend and the proportion of early-stage breast cancer increased between 2006 and 2014. We report the highest LR rates in this young population were associated with HR-/HER2+ tumors.